Uncertainty in Ex-Ante Poverty and Income Distribution : Insights from Output Growth and Natural Resource Country Typologies - Mendez Ramos, Fabian (World Bank, Washington, DC, 2019)
This paper studies future poverty, inequality, and shared prosperity outcomes using a panel data set with 150 countries over 1980-2014. The findings suggest that global extreme poverty will decrease in absolute and relative terms in the period 2015-2030. However, absolute poverty is likely to increase by 2030 in resource-output oriented countries and economies with low rates of output per capita growth. Countries with high growth rates of output are expected to achieve poverty levels below 3 percent by 2030. Global and country aggregations show a decrease in income inequality by 2030; though, significant downside risks could increase wealth inequality in high- and low-output growth economies by 2030. Substantial uncertainty, as measured by the variability of the simulated outcomes, exists on shared prosperity gaps across the studied country typologies.